Transportasi Publik Meningkatkan Ekonomi Hijau Secara Berkelanjutan di Jakarta - Nabila Putri Wahiddiyah; Nuraida Rezeki Fadilah; Dianita Zahra Zafira; Anisa Surya Lestari; Muhammad Rahmat Alwafi; Shahibah Yuliani (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Jakarta as a metropolitan city with a high level of mobility has complex problems, one of which is air pollution that has been rooted for a long time. The main source of air pollution is motor vehicle pollution with an increase in the number of motorized vehicles from year to year obtaining a daily average index of PM2.5 reaching 45µg/m³ far above the WHO safe threshold. This literature review research was conducted to reveal that the integration of sustainable public transportation in Jakarta has successfully reduced pollution emissions and improved transportation efficiency. The results found that the application of the Green Economy concept not only affects the economic sector in general, but also public transportation. In Jakarta, public transportation has become a major means of realizing Green Economy principles, such as reducing carbon emissions, using renewable energy, and increasing resource efficiency. the change of society from the use of private vehicles to public transportation can significantly reduce greenhouse gas emissions, which is in accordance with sustainable development goals. Therefore, the purpose of this research is to review and analyze public transportation as an alternative solution in improving the green economy.